The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0238310
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of labor satisfaction and predictor of postnatal satisfaction in the north-east of Peninsular Malaysia

Abstract: Introduction Identifying the factors contributing to maternal satisfaction is a proxy measure to improve the quality of care. It evaluates the health service provision by understanding maternal perceptions and expectations and promoting adherence to health services. This study aimed to identify the sociodemographic, obstetric, and medical factors contributing to labor satisfaction among postpartum women and examine the association between labor and postnatal satisfaction. Methodology A cross-sectional study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Women who were satisfied with delivery care services were 2.05 times more likely to be satisfied with immediate PNC than women who were not satisfied with delivery care services. This study finding was supported by the studies done in West Shewa, Ethiopia 14 and Malaysia 22 The possible explanation for this finding could be that satisfaction is influenced by previous experiences. Thus, a good experience contributes to building confidence and trust toward health services in general.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Women who were satisfied with delivery care services were 2.05 times more likely to be satisfied with immediate PNC than women who were not satisfied with delivery care services. This study finding was supported by the studies done in West Shewa, Ethiopia 14 and Malaysia 22 The possible explanation for this finding could be that satisfaction is influenced by previous experiences. Thus, a good experience contributes to building confidence and trust toward health services in general.…”
Section: Discussionsupporting
confidence: 83%
“…This finding was consistent with studies done in Nepal 28 and Malaysia. 22 This may be explained by multiparous women who may reflect their expectations based on prior experiences compared to primiparous women. Conversely, primiparous women may have a higher expectation and perceive that transition to motherhood was fearful and they need more time to be with the health-care provider to get more information, support, care, and assistance with baby care, breastfeeding, and their postnatal care, 33 which may lead them to be less satisfied with immediate PNC than multiparous women in immediate PNC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women allocated continuous labour support were less likely to report negative feelings about their childbirth experience (RR 0.69, 95% CI 0.59 to 0.79) [32]. A recent local study by Adnan et al, demonstrated that women whose pregnancies were labelled as at-risk and required more attention by health workers reported greater levels of labour satisfaction than their low-risk counterparts [33]. Factors that influence maternal satisfaction toward the quality of nursing care during birth include caregiver and woman interaction, as well as woman's involvement in the caring process [34].…”
Section: Discussionmentioning
confidence: 99%